FACTORS INFLUENCING COMPLIANCE WITH THE NATIONAL ANTIMALARIAL TREATMENT GUIDELINES BY FACILITY-BASED SECONDARY HEALTH CARE PHYSICIANS IN OYO STATE, NIGERIA (2015)
The National Antimalarial Treatment Guidelines (NATG) stipulates treatment actions for the management of malaria using Artemisinin Combination Therapy (ACT). Available evidence indicates that adoption of treatment guidelines are not matched with corresponding levels of comprehension and compliance. An investigation of practice gaps will generate information which will guide future policy formulation and implementation. The aim of this study was to determine the factors influencing compliance of facility-based secondary health care physicians in Oyo state with NATG. This descriptive cross-sectional study involved 94 out of 124 physicians on full-time employment from all 36 secondary health care facilities offering malaria management services in Oyo state. They were interviewed using a semi-structured interviewer-administered questionnaire to elicit information on awareness of and perceived challenges relating to implementation of the NATG. This included a 60-point knowledge scale on diagnosis and treatment of malaria with knowledge scores of 0-20, >20-40 and >40-60 rated as poor, fair and good respectively. Case notes of malaria patients seen on the day of interview were stratified into three categories; under-five children, pregnant women and adults. A minimum of one and maximum of three case notes were randomly selected across the strata per physician. Overall, 44, 74 and 128 case notes belonging to pregnant women, under-five children and adults respectively were assessed using a check-list which included an 11-point compliance scale on patient’s history documented, laboratory assessment and drug prescribed by dosage. Compliance scores of 0-3, >3-7 and >7-11 were rated poor, fair and good respectively. Data were analysed using descriptive statistics and t-test at p=0.05. Age of respondents was 40.0±8.6 years, 70.2% were males and mean years of experience was 9.4±3.4. Majority (84.0%) of the respondents had ever received training on NATG, 91.5% of the respondents had heard of the NATG mainly from medical conferences. However, 48.9%, 37.2% and 11.7% had seen, read and have personal copies of NATG respectively. Knowledge score was 32.4±6.4 with 8.5% and 90.4% of respondents having good and fair knowledge of the NATG respectively. Compliance score was 4.3±1.9 with 4.5%, 63.4% and 32.1% of physicians having good, fair and poor compliance respectively. Only 0.8% of case notes had complete history documented, 54.0% had prescription for ACT, 19.1% Sulphadoxine Pyrimethamine and 26.9% non-recommended Anti-Malarial Drugs. Recommended dosage of ACT was correctly prescribed in 26.0% and 47.8% of case notes belonging to children and adults respectively. Only 24.2% of adults and 5.6% of children had both clinical and laboratory assessments before prescription. High cost (31.4%), unavailability (14.9%) and treatment inefficacy (9.1%) of ACTs were identified as perceived hindrances to compliance with NATG. A statistically significant higher compliance score (4.4±1.7) was observed amongst respondents ever trained on NATG than those never trained (3.7±1.3). An interplay of factors influenced physician’s compliance with the national antimalarial treatment guidelines. Continuing professional training programmes on compliance with current malaria treatment approaches and adequate supervision are recommended.